The Characteristics of the Concise Exegesis of the Holy Qur’an published by LPMQ of Ministry of Religious Affairs of Indonesia - Yudi Setiadi; Muhamad Tamamul Iman; Muhammad Farkhan (JURNAL INDO-ISLAMIKA, 2021)
This research explores and examines the characteristics of the Concise Exegesis of the Holy Qur’an published by Appraisal Agency of Qur’anic Manuscripts (LPMQ) of Ministry of Religious Affairs of Indonesia (Kemenag RI). The primary data of this study is the manuscript of LPMQ’s Concise Exegesis of the Holy Qur’an. Apart from that, this research also uses secondary data from other resources such as books and journal articles. In this regard, this research is library research. The concise exegesis book is analyzed using the methodology of Qur’anic interpretation proposed by Islah Gusmian in his book entitled ‘Khazanah Tafsir Nusantara’ (Nusantara’s Qur’anic Exegesis Heritage). This article outlines some important constructive remarks for future publication of the book. The remarks are as follow: 1) the naming consistency; 2) the consistency of the exegesis presentation structure; 3) the problem of verses’ translation writing format.